Exploring the Impacts of Online Chat on Well-Being and Job Engagement in a Higher Education Work Environment - Yordudom, Tanakrit; Imjai, Narinthon; Suwannual, Patchlada; aujirapongpan, somnuk (Journal of Multidisciplinary in Social Sciences, 2024)
Despite extensive research into the impacts of digital communication on well-being and job engagement, the specific effects of online chatting within these domains have been less explored, particularly in the context of Thailand's higher education sector. This quantitative study investigates the implications of online chatting on well-being and job engagement among 126 university lecturers in Thailand, with a demographic breakdown of 61.9% female and 37.3% male participants. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), the research examines three hypotheses: the impact of online chat on well-being (H1), online chat on job engagement (H2), and well-being on job engagement (H3). The findings reveal a significant negative impact of online chat on well-being (β = -0.236, p = 0.003), while the relationship between online chat and job engagement was not supported (β = -0.047, p = 0.642). Conversely, a strong positive relationship was observed between well-being and job engagement (β = 0.609, p < 0.001), underscoring well-being as a significant mediator between online chat and job engagement. These results highlight the nuanced role of online chat in the academic work environment, suggesting that while it may pose challenges to well-being, it also has the potential to indirectly enhance job engagement through improved well-being. The study's focus on a specific academic context and its reliance on self-reported data suggest caution in generalizing the findings, pointing to avenues for future research in broader demographic and occupational settings.